Assessing the Risk of Spatial Spreading of Diseases in Hospitals - Lu, Dan; Aleta, Alberto; Moreno, Yamir (Frontiers in Physics, 2022)
In recent years, the transmission of healthcare-associated infections (HAIs) has led to substantial economic loss, extensive damage and many preventable deaths. With the increasing availability of data, mathematical models of pathogen spreading in healthcare settings are becoming more detailed and realistic. Here, we make use of spatial and temporal information that has been obtained from healthcare workers (HCWs) in three hospitals in Canada and generate data-driven networks that allow us to realistically simulate the spreading of an airborne respiratory pathogen in such settings. By exploring in depth the dynamics of HAIs on the generated networks, we quantify the infection risk associated with both the spatial units of the hospitals and HCWs categorized by their occupations. Our findings show that the ``inpatient care'' and ``public area'' are the riskiest categories of units and ``nurse'' is the occupation at a greater risk of getting infected. Our results provide valuable insights that can prove important for measuring risks associated with HAIs and for strengthening prevention and control measures with the potential to reduce transmission of infections in hospital settings.